The Agonistics of Reading: Playing, Gambling, Committing - Olivier Hercend (Angles)
From Michel Picard’s La lecture comme jeu to Umberto Eco’s model of the “game of chess”, reading has often been compared to a kind of game. Games serve as a useful template of interaction, highlighting both the exterior set of rules governing an activity, and the agency that these rules leave to the individual. Yet games are also a constitutive human activity, with myriads of variants, from the free play of children to the gambler’s thrill to the highly ritualized sets of actions and reactions seen in martial arts or chess. This article proposes to review classical and contemporary theories of reading based on their specific use of the metaphor of reading as a game. It first presents the structuralist and phenomenological approaches, which tend to define reading as a performance based on pre-established rules, like a game of chess. It then delves into theories that instead choose to highlight the incalculable aspect of every new reading, the possibility for the reader to go off the beaten path. These tend to see reading more as a game of chance than a game of chess. This does not mean, however, that they construe reading as licentious: gambles involve stakes. Theories like Jean-Jacques Lecercle’s Marxist pragmatics are most specific in explaining what the reader is actually committing to. The stance we take, our interaction with texts as “interpellations”, are part and parcel of our lives as social and political beings. They are the products of a certain context, but they may in turn influence or call into question the very structures that make them possible. This is why this article suggests reading be examined through the notion of agonistics. Taking up the ancient Greek word “agôn”, which implies that games are forms of trial made to reveal something of the player’s nature, the agonistics of reading posits that reading must not be seen as an isolated phenomenon. On the contrary, the challenge that texts pose, to confront them or to accept them, is fundamental in the construction of our identity as readers and as human beings. This dialectics of self-revelation and self-construction, through the interaction with texts, is the often unspoken yet decisive game that every reader plays.